Chalazion with cutaneous horn. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
Initially we thought about the possibility of a molluscum contagiosum because by typing skin horn and eyelid in PubMed we had found some cases of molluscum contagiosum of the eyelid free rim surmounted by a skin horn (1, 2) and also because theoretically the skin horn could be an exaggeration of the superficial horny plug often present in molluscum contagiosum. Although the opinion of the ophthalmologist and family history supported the diagnosis of chalazion, we did not find any case of horn on chalazion in PubMed. We recommended a timolol ophthalmic gel due to the site of the lesion and aiming at inhibiting the inflammatory angiogenesis and mechanically urging the horn. The regression of the inflammatory papule, the fall of the horn and the absence of molluscum contagiosum bodies on histological examination confirmed the diagnosis of cutaneous horn on chalazion.